Mangrove Organic Batik E-Module Model in Batik Lessons - Sinukaban, Veronica Yulisna; Lapisa, Remon; Maksum, Hasan; Rahmiati (JTP - Jurnal Teknologi Pendidikan, 2024)
The State Vocational High School (SMK) 1 Berastagi is a tourism cluster school that in the learning process is still conventional, so the learning results of batik have not met the competency standards. This is indicated because students do not have a background in batik. Knowledge development introduces modules as alternative teaching materials that are able to improve student learning outcomes effectively and efficiently. The purpose of this research is to, 1) produce valid, practical and effective batik learning e-modules, 2) develop learning e-modules on batik materials for Vocational High Schools. This type of research is Research and Development, with the achievement of designing and making batik e-modules, then the results of validity, practicality and effectiveness tests, with data analysis techniques consisting of validity, practicality and effectiveness analysis. The data was analyzed using the Likert scale, the object of the research was grade XI students of SMK Negeri 1 Berastagi. The data from the research results obtained shows that the batik learning e-modules produced in the valid, practical and effective categories both in terms of the feasibility of the content of the e-module, the language of the e-module, the presentation of the e-module and the graphics of the e-module. It can be concluded that the batik learning e-module is worthy of being used as an alternative reference material in the development of the Batik e-module.